Peningkatan Kapasitas Sumber Daya Manusia PAUD dengan Pelatihan Bahasa Inggris Di Kecamatan Nanggulan Kabupaten Kulon Progo Yogyakarta - Yashinta Farahsani; Margaretha Dharmayanto Harmanto (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Community service activities, specifically the Community Partnership Program (PKM), aims to improve the ability of Early Childhood Education (PAUD) teachers, both in terms of pronunciation and the methods that support it in Nanggulan sub-district, Kulon Progo district. The target audience for this service program are the PAUD teachers in SPS Tunas Harapan, which amount to 4 (four) people. The programs that have been implemented are training 1) How to pronounce English words, and 2) English methods for PAUD level. The overall process of science and technology transfer is carried out with a pattern of education and training that is equipped with socialization to these teachers to improve the ability and skills to use English developed through English language training (pronunciation on pronunciation or pronunciation) and methods and benefits to improve teacher ability and school quality.